On multiple M2-brane model(s) and its N=8 Superspace Formulation(s) - I. A. Bandos (Acta Polytechnica, 2010)
We give a brief review of Bagger-Lambert-Gustavsson (BLG) model, with emphasis on its version invariant under the volume preserving diffeomorphisms (SDiff3) symmetry. We describe the on-shell superfield formulation of this SDiff3 BLG model in standard N = 8, d = 3 superspace, as well as its superfield action in the pure spinor N = 8 superspace. We also briefly address the Aharony-Bergman-Jafferis-Maldacena (ABJM/ABJ) model invariant under SU(M)k × SU(N)−k gauge symmetry, and discuss the possible form of their N = 6 and, for the case of Chern-Simons level k = 1, 2, N = 8 superfield equations.